Whether Urban Development and Ecological Protection Can Achieve a Win-Win Situation—The Nonlinear Relationship between Urbanization and Ecosystem Service Value in China - Yingtao Wu (Sustainability, 2019)
Most of the existing research on urbanization suggests that urbanization leads to a decline in ecosystem services values (ESV). However, the impacts of industrial structure and changes in land use patterns on ESV have often been ignored. Using provincial data in China from 2003 to 2015, this study demonstrates the possibility of achieving a win-win situation regarding urbanization and ESV enhancement at the global and regional scales. The negative effect from production processes and the influence of residents’ preferences are considered in the evaluation of ESV. The impact of urbanization on ESV is empirically analyzed by using a spatially adaptive semi-parametric model in order to mitigate both endogeneity of the parametric model and the curse of dimensionality in nonparametric model. The results show that there is a U-shaped curve relationship between urbanization and ESV for the whole country. However, most provinces of China are still located at the left side of the U-shaped curve where urbanization reduces the ESV per capita. Central and local governments should strengthen differentiated land use policies, environmental regulations, and finance and tax policies to transform the industrial structure, so that each province may achieve a win-win situation regarding urbanization and ESV enhancement. Such policy changes would promote sustainable development in China.